PENGARUH PROGRAM IISMA TERHADAP PENINGKATAN KEMAMPUAN KOMUNIKASI ANTARBUDAYA: STUDI NARATIF - Aaliyah Zahirah Setiawan Bahrie (Puslitabmas Batam Tourism Polytecnic, 2025)
This study explores the impact of the Indonesian International Student Mobility Awards (IISMA) program on improving intercultural communication skills, based on the researcher’s personal experience as an IISMA participant at the National Kaohsiung University of Hospitality and Tourism (NKUHT), Taiwan. Using a narrative qualitative approach, the research highlights the challenges and strategies of adapting to a Mandarinspeaking environment and engaging in multicultural activities, both academically and socially. Key findings reveal that IISMA significantly enhanced the researcher’s flexibility and empathy in communication through workshops, industry visits, and cultural exchanges. These experiences not only broadened cultural insights but also fostered interpersonal relationships in a multicultural setting. The study underscores IISMA’s role as a strategic platform in equipping Indonesian students with global competencies and adaptability in international contexts.